β-Glucans as Dietary Supplement to Improve Locomotion and Mitochondrial Respiration in a Model of Duchenne Muscular Dystrophy - Letizia Brogi (Nutrients, 2021)
Duchenne muscular dystrophy (DMD) is a severe X-linked neuromuscular childhood disorder that causes progressive muscle weakness and degeneration. A lack of dystrophin in DMD leads to inflammatory response, autophagic dysregulation, and oxidative stress in skeletal muscle fibers that play a key role in the progression of the pathology. β-glucans can modulate immune function by modifying the phagocytic activity of immunocompetent cells, notably macrophages. Mitochondrial function is also involved in an important mechanism of the innate and adaptive immune responses, owing to high need for energy of immune cells. In the present study, the effects of 1,3-1,6 β-glucans on five-day-old non-dystrophic and dystrophic (sapje) zebrafish larvae were investigated. The effects of the sonication of β-glucans and the dechorionation of embryos were also evaluated. The results showed that the incidence of dystrophic phenotypes was reduced when dystrophic embryos were exposed to 2 and 4 mg L−1 of 1,3-1,6 β-glucans. Moreover, when the dystrophic larvae underwent 8 mg L−1 treatment, an improvement of the locomotor performances and mitochondrial respiration were observed. In conclusion, the observed results demonstrated that 1,3-1,6 β-glucans improve locomotor performances and mitochondrial function in dystrophic zebrafish. Therefore, for ameliorating their life quality, 1,3-1,6 β-glucans look like a promising diet supplement for DMD patients, even though further investigations are required.